Fundamentals of Financial Management / Twelfth Edition - Brigham Eugene F; Houston Joel F (South-Western - Cengage Learning, 2009)
This book allows to access financials, earnings estimates, market data and Excel worksheets from thousands of domestic and international companies. Preface, Introduction to Financial Management, An Overview of Financial Management, Fundamental Concepts in Financial Management, Financial Markets and Institutions, Financial Statements and Cash Flow and Taxes, Analysis of Financial Statements, Time Value of Money, Financial Assets, Interest Rates, Bonds and Their Valuation, Risk and Rates of Return, Stocks and Their Valuation, Investing in Long-Term Assets: Capital Budgeting, The Cost of Capital, The Basics of Capital Budgeting, Cash Flow Estimation and Risk Analysis, Real Options and Other Topics in Capital budgeting, Capital Structure and Dividend Policy, Capital Structure and Leverage, Distributions to Shareholders: Dividends and Share Purchases, Working Capital Management and Financial Forecasting, Working Capital Management, Financial Planning and Forecasting, Special Topics in Financial Management, Derivatives and Risk Management, Multinational Financial Management, Mergers and Acquisitions, Appendixes, Index.